A new record of Megatoma (Pseudohadrotoma) graeseri (Coleoptera: Dermestidae: Megatominae) from Manitoba, Canada - Háva, Jiří (Zootaxa, 2013)
Megatoma (Pseudohadrotoma) graeseri (Reitter, 1887), an eastern Palaearctic species, is newly recorded in North America, with specimens reported from Manitoba, Canada.